Tramadol Potentiates Vasopressin Induced Analgesia in Albino Mice - G. Tyagi*, Ayesha Sulthana, Nidhi Tyagi; Manoj (Recent Research in Science and Technology, 2011)
The effect of centrally acting opioid analgesic Tramadol on vasopressin induced analgesia was evaluated in Swiss albino mice. Analgesia was evaluated in the mice using tail clip and writhing test techniques. Animals were divided into control and test groups (n=6). Arginine vasopressin (12 Ã‚Âµg/kg i.p) and its synthetic analogue, Terlipressin (300 Ã‚Âµg /kg i.v) injected in the mice produced analgesia by increasing the latency period by 131.6% and 53.5% respectively and reduced the acetic acid writhing by 45.85 % and 13.51 % respectively. Pretreatment with Tramadol (10 mg/kg i.p) potentiated the analgesic action of vasopressin and terlipressinÃ‚Â and increased the latency period and reduced the acetic acid induced writhings respectively. This study suggests that Tramadol can be combined with vasopressin for enhanced analgesic effect.